The Role of Social Ties in Supporting Digital Literacy Among Older Adults in Italy During Times of Crisis and Change - Ruspini, Elisabetta; Mancassola, Anita; Quartararo, Cristina Incoronata (Italian Sociological Review, 2025)
This study focuses on the role of social ties in supporting digital literacy among older adults in Italy. It explores, on one hand, the influence of intergenerational family support on the digital engagement of older individuals – specifically their use of PCs, smartphones, and the Internet. On the other hand, it investigates the contribution of broader social networks, such as voluntary organizations and community associations, in promoting technology use among older women and men. The findings highlight how different types of relationships and networks interact to support digital literacy among older adults. They emphasize the important role of both family and broader social support in helping to reduce the age-related digital divide, especially during times of crisis and change. The study also offers valuable insights for shaping existing policies and developing new ones aimed at enhancing digital inclusion among older people. The paper draws upon data collected by ILQA-19-Longitudinal Study on Older People’s Quality of Life, aimed at investigating the social consequences of the Covid-19 pandemic on older people’s well-being and everyday life. The first wave of data collection was conducted in the spring of 2020 through semi-structured video interviews with a sample of 40 men and women aged 65 to 80, living in ten villages in the northern part of Italy (Province of Lodi, Lombardy), which experienced the first lockdown in Europe.